Exploring the interplay between structure and agency in the context of higher education in North Macedonia: a qualitative study on the experiences of early career academics - Martin, G (2021)
This qualitative study examines the experiences of early career academics (ECAs) in contemporary North North Macedonia and sets out to understand how the interplay between specific academic workplace structures and the agency of ECAs unfolds on a day-to-day basis and over their career trajectories.